Contributo para o conhecimento do concelho de Arraiolos: o projeto LAPA - Rocha, Leonor (2013)
The project “Levantamento Arqueológico e Patrimonial de Arraiolos – LAPA”, responsibility of the signatories, aims to review and update the data archaeological and heritage related to the territory of Arraiolos, Évora, Portugal. The field work in the last three years focused on areas that were with larger gaps in research, either because there is an apparent void, either because the existing information was reported on ancient works. The results obtained allowed to fill some of the gaps and significantly expand the universe of known sites especially with regard to the Recent Prehistory and Roman era. This communication aims to present the different types of findings identified to date in this area, while seeking to understand the population dynamics associated.